ANALISIS FAKTOR KINERJA DALAM MENINGKATKAN PRODUKTIVITAS KARYAWAN PRODUKSI PT. SINAR MAS MEGAH STEEL SURABAYA - Fitriya Gemala Dewi, Muharom, Krisnadhi Hariyanto, Subaderi, (Journal of Industrial Engineering and Technology, 2024)
The point investigate is to depict and examine these variables that impact the execution of PT. Sinar Mas Megah Steel Surabaya. These components are gathered into 2 (two) : person measurements (capacity, work involvement, inspiration) and organizational measurements (pioneers, interaction, work environment), whereas in light of worker execution is the variable, and the work comes about illustrated by workers depending on at a specific moment benchmarks. indicated execution. That investigate test comprised of 60 representatives partitioned into a few divisions. This overview was created by analysts employing a 5-point Likert scale. Information examination strategies utilize expressive measurements and different straight relapse. Different straight relapse models with six free factors can clarify 53.5% of the variety in representative execution factors. It observes in portion six free factors in investigate inquire about, the employee's capacity to have the most prominent impact on representative execution.